Bacterial Profile and Pattern of Antimicrobial Drug Resistance in Diabetic Foot Ulcers at Tertiary Care Hospital - S K Chavan; G S Karande; K B Chavan (International Journal of Medical Research and Review, 2015)
Background: Worldwide diabetic foot is a major medical problem leading to disability and economic instability to family and country.Objectives: To assess the clinical and bacteriological profile of diabetic foot ulcer among rural Indian residents. Also to know the prevalent pattern of antimicrobial resistance of most commonly isolated organisms to various currently in use antimicrobial agents.Methodology: From 78 cases of diabetic foot ulcer, identification of isolates was done using standard microbiological techniques. Antibiotic sensitivity testing were carried out followed by detection of ESBL, MRSA, AmpC and MBL producing strains as per the CLSI guidelines.Results: In our study, a total of 78 specimens were cultured and 97.4% ulcer showed growth of organisms (76/78). Of the total 139 isolates, 134 (96.4%) were aerobes and only 5 (3.6%) isolates were anaerobes. An average of 1.8 organisms per lesion was isolated. Among the aerobes, 93 (69.4%) gram negative and 41 (30.6%) gram positive organisms were isolated. Pseudomonas aeruginosa 23.9% was predominant organism followed by Klebsiella species (20.9%). A total 41 (30.6%) aerobic gram positive bacteria were isolated. Staphylococcus aureus was the most common gram positive organism 28.4% in which Methicillin resistant S. aureus (MRSA) was 57.9%. Among gram negative organisms 46(49.5%) isolates showed ESBL production. Among ESBL producing strains Escherichia coli 68.3% isolates recorded highest ESBL activity followed by Pseudomonas aeruginosa 62.5 % and Klebsiella species 53.6 %.Conclusion: The present study has shown that diabetic foot infections are polymicrobial in nature and commonly caused by multi drug resistant gram negative organisms.